2018
DOI: 10.1016/j.jtcme.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous extract of Carica papaya Linn. roots potentially attenuates arsenic induced biochemical and genotoxic effects in Wistar rats

Abstract: In Africa, the fruit, leaf, seed and roots of Carica papaya Linn. are generally used to treat a variety of diseases such as malaria, cancer, and cardiovascular diseases. In this study, we evaluated the protective potentials of aqueous extract of C. papaya roots on arsenic-induced biochemical and genotoxic effects in Wistar rats. Rats were induced intraperitoneal with sodium arsenate (dissolved in distilled water at 3 mg/kg body weight) for 21 days and the animals were administered simultaneously with 200 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…e leaves are thought to increase breast milk and used in the treatment of tonsillitis, ulcerative stomatitis, and gingivitis [12]. e roots have been suggested to be beneficial in managing arsenic poisoning [13]. Different preparations from the leaves have found use in managing haemorrhoids, management of asthma, treatment of urinary tract infections, poultice for sores [12], and treatment of helminth infections [14].…”
Section: Introductionmentioning
confidence: 99%
“…e leaves are thought to increase breast milk and used in the treatment of tonsillitis, ulcerative stomatitis, and gingivitis [12]. e roots have been suggested to be beneficial in managing arsenic poisoning [13]. Different preparations from the leaves have found use in managing haemorrhoids, management of asthma, treatment of urinary tract infections, poultice for sores [12], and treatment of helminth infections [14].…”
Section: Introductionmentioning
confidence: 99%
“…Papaya (Carica papaya L.) is a perennial plant with a rapid growth, and it provides fruits for more than twenty years [1]. Papaya is considered one of the most important fruits worldwide because of its high contents of ascorbic acid, provitamin A, calcium, and carotenoids [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although the ameliorative effects of both the CPE and MIE on atrazine-induced toxicity in fish have not been reported so far, previous studies have suggested the in vivo ameliorative potentials of the two extracts against toxins in mammalian models (Adeneye et al, 2015;Awodele et al, 2016;Ojo et al, 2018). The results of these studies are in tandem with those observed in the present study regarding the prevention of leakage of tissue enzyme biomarkers from the cytoplasm, where they are originally domiciled, into adjacent cells and general circulation, and the antioxidant property of the extracts.…”
Section: Discussionmentioning
confidence: 99%